ChemInform Abstract: Aldol Reactions of 1, 2‐Diketones Catalyzed by Amines to Afford Furanose Derivatives. Issue 23 (June 2015) - Jithender, Enukonda; Katsuyama, Isamu; Zhang, Dongxin; Johnson, Sherida; Tanaka, Fujie
Abstract The reaction of acyclic 1, 2‐diketones with electron deficient aryl aldehydes proceeds with high regioselectivity which is controlled by the catalyst used.